Oncogenic retinoic acid receptor γ knockdown reverses multi-drug resistance of human colorectal cancer via Wnt/β-catenin pathway. Issue 7 (3rd April 2017) - Huang, Gui-Li; Song, Wei; Zhou, Pan; Fu, Qi-Rui; Lin, Chen-Lu; Chen, Qing-Xi; Shen, Dong-Yan
ABSTRACT: Retinoic acid receptor γ (RARγ), a unique member of the nuclear receptor superfamily, plays an important role in the progression of several cancers such as hepatocellular carcinoma, esophageal cancer, and cholangiocarcinoma. However, little is known about the regulatory mechanism of the RARγ expression in colorectal cancer (CRC) progression. In the present study, we found that RARγ was frequently overexpressed in human CRC specimens and CRC cell lines, and it mainly resided in the cytoplasm in CRC specimens. Tissue microarrays showed that RARγ indicated vital clinical significance in CRC. RARγ knockdown neither affected CRC cell proliferation nor blocked the cell cycle of CRC cells. However, RARγ knockdown increased the sensitivity of CRC cells to chemotherapeutics through downregulation of multi-drug resistance 1(MDR1). Further studies suggested that RARγ knockdown resulted in downregulation of MDR1, in parallel with suppression of the Wnt/β-catenin pathway. Moreover, a significantly positive association between RARγ and MDR1 was demonstrated in CRC tissue microarrays. Collectively, these results suggested that overexpression of RARγ contributed to the multidrug chemoresistance of CRC cells, at least in part due to upregulation of MDR1 via activation of the Wnt/β-catenin pathway, indicating that RARγ might serve as a potential therapeutic target for chemoresistant CRC patients.